2019
DOI: 10.1109/tcyb.2018.2789889
|View full text |Cite
|
Sign up to set email alerts
|

Taste Recognition in E-Tongue Using Local Discriminant Preservation Projection

Abstract: Electronic tongue (E-Tongue), as a novel taste analysis tool, shows a promising perspective for taste recognition. In this paper, we constructed a voltammetric E-Tongue system and measured 13 different kinds of liquid samples, such as tea, wine, beverage, functional materials, etc. Owing to the noise of system and a variety of environmental conditions, the acquired E-Tongue data shows inseparable patterns. To this end, from the viewpoint of algorithm, we propose a local discriminant preservation projection (LD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“…In previous studies, the application of subspace learning and support vector machine algorithms in electronic tongue (Zhang, Wang, Huang, Liu, & Tan, 2019) and electronic nose (Zhang, Liu, & Deng, 2017) have been investigated, and good prediction (98% accuracy) was achieved. However, detection and of cocoa fermentation in natural condition using e-nose was not reported.…”
Section: Rf Is Constructed By Multiple Decision Trees and When A New mentioning
confidence: 99%
“…In previous studies, the application of subspace learning and support vector machine algorithms in electronic tongue (Zhang, Wang, Huang, Liu, & Tan, 2019) and electronic nose (Zhang, Liu, & Deng, 2017) have been investigated, and good prediction (98% accuracy) was achieved. However, detection and of cocoa fermentation in natural condition using e-nose was not reported.…”
Section: Rf Is Constructed By Multiple Decision Trees and When A New mentioning
confidence: 99%
“…As an example, the MSPV is proved to be the best waveform for classifying different yogurts. 17 In 2018, the study by Zhang et al 10 showed an electronic tongue based on an MLAPV technique. This electronic tongue followed the electrodes setup of Tian et al 16 In the e-tongue, five electrodes, made of gold, platinum, palladium, tungsten, and silver, were chosen as working electrodes, whose responses are illustrated in Figure 3.…”
Section: Mlapvmentioning
confidence: 99%
“…In 2018, Zhang et al 10 conducted a research, where they showed that due to the noise of the system and a variety of environmental conditions, the data acquired by an electronic tongue show inseparable patterns. To solve this phenomenon, from the point of view of the algorithm, they proposed an LDPP model.…”
Section: Data Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local discriminant preservation projection (LDPP) model was proposed from the perspective of algorithm. Kernelized extreme learning machine (KELM) classifier model based on LDPP achieved optimal taste recognition performance with an accuracy of 98% [22]. Some researchers have improved the accuracy of fruit juice recognition through the fusion of electronic tongue and electronic nose [23].…”
Section: Introductionmentioning
confidence: 99%